Assessment of frequency selectivity with psychoacoustic masking curves - ŁĘTOWSKI, T.R.; NABELEK, A.K. (Archives of Acoustics, 1995)
Psychophysical tuning curves (PTCs) and narrow-band masking curves (NMCs) were obtained for three frequencies: 500, 1600, and 2500 Hz, using the Bekesy tracking method. Comparisons of the data obtained for seven normal and one slightly impaired ears indicate that PTCs measured at 20 dB SL and NMCs measured at 40 dB SL seem to be equally effective in describing frequency selectivity using Q(10) criterion. Therefore, the choice of either methodology for assessment of frequency resolution may be dictated by its convenience and avilable instrumentation. Due to dependence of PTCs and NMCs on signal presentation level, the conclusions of this study are limited to normally hearing listeners. It is yet to be shown whether and within what range of hearing loss both measures can be treated as equivalent at higher presentation level.